Genetic variability, correlation and path analysis in Neolamarckia cadamba (Roxb.) Bosser - Selvan R., Thirunirai; Parthiban, K.T. (Indian Journal of Agroforestry, 2020)
Twenty-five Neolamarckia cadamba clones were evaluated for variability, heritability and genetic advance studies based on the growth attributes viz., basal diameter, diameter at breast height (DBH), height, number of branches, volume, leaf length, leaf width, leaf petiole length, total number of leaves, leaf area and volume. Genotypic co-efficient of variation was lower than the phenotypic co-efficient of variation for all the growth traits. Among the genotypic co-efficient of variation, volume recorded higher GCV (57.46%), followed by leaf area (26.55%), total number of leaves (25.33%), DBH (24.61%) and height (22.42%). Heritability was relatively higher for four growth attributes viz., height (68.35%), basal diameter (59.00%), DBH (54.18%) and volume (47.93%), and lower for leaf petiole length (20.46%). Higher genetic gain was attributed to volume (81.95%), followed by height (38.16%) and DBH (37.32%). Genotypic correlations were higher than the phenotypic correlation for all the growth traits which indicated the use of variability of these attributes for further tree improvement program. These relationships will help in selecting one or other traits for treeÂ improvement. Among growth traits, leaf area (0.971) registered highest direct positive effect on volume, followed by total number of leaves (0.767), height (0.351), DBH (0.175) and basal diameter (0.121), and maximum indirect effect on volume registered by leaf length (0.970) and leaf width (0.958) through leaf area. Hence, for the selection of better clone to maximize the volume, the characters viz., DBH, height, leaf area, total number of leaves, leaf length and leaf width could be used as selection criteria in this multipurpose species.